Influence of respiration‐induced B0 variations in real‐time phase‐contrast echo planar imaging of the cervical cerebrospinal fluid. Issue 2 (7th April 2019) - Peters, Kristina; Weiss, Kilian; Maintz, David; Giese, Daniel
Abstract : Purpose: Respiration induces temporal variations of the main magnetic field B0 along the spinal cord. These variations are typically not compensated for in velocity quantifications using phase‐contrast MRI. The goal of this study was to analyze errors caused by respiration‐induced B0 variations in real‐time phase‐contrast echo planar imaging (PCEPI) of cervical cerebrospinal fluid (CSF) velocity measurements and to evaluate this effect for various sequence parameters using numerical simulations. Methods: Real‐time B0 measurements with double gradient echo sequence and PCEPI measurements were acquired in the cervical CSF of 10 healthy subjects. Dynamic phase offsets attributed to respiration‐induced B0 variations were analyzed by quantifying amplitudes and comparing the temporal behavior with respiratory signals. In experiments and simulations, the influence of the echo time (TE) and the delay between PCEPI images (Δ t ) with respect to respiration on the dynamic phase offsets were investigated. Results: A good agreement was found between phase offsets extracted from both acquisition types. Furthermore, respiratory signals qualitatively matched the temporal behavior of the measured phase offsets showing a dependency on subject‐dependent local B0 distribution and respiration physiology. Simulations revealed residual background phases in PCEPI velocity quantification varying with TE and Δ t . Conclusion: Respiration‐induced B0 variations result in dynamic background phases in real‐time PCEPI velocity quantifications of the CSF in the cervical spine. The current work underlines that these background phases need to be corrected to avoid confounding effects.